Accounting for uncertain tax positions and lenders’ risk evaluations - Lee, Sungsil (eJournal of Tax Research, 2023)
This study explores whether publicly traded US firms’ unrecognised tax benefit (UTB) disclosures are associated with the cost of debt. Using UTB comovement, a measure of UTB comparability, I find that the UTB balance is positively associated with the cost of debt, but this association is less pronounced when UTB disclosures are comparable to those of other firms. In addition, these associations are more predominant when firms have a considerable amount of foreign sales or engage in research and development (R&D) activities.
Keywords: cost of debt; tax risk; tax uncertainty; uncertain tax positions; unrecognised tax benefit (UTB)